(untitled) (Eduscotech, 2022)
The Merdeka Curriculum emphasizes flexibility, autonomy, and contextualized learning to meet students’ diverse needs across Indonesia. This community service program aims to examine the implementation of a curriculum development workshop for English teachers at the junior high school (SMP), senior high school (SMA), vocational high school (SMK), and Islamic senior high school (MA) levels in Maospati District. The workshop was designed to strengthen teachers’ understanding of the core principles of the Merdeka Curriculum and to improve their ability to design interactive, creative, and 21st-century competency-based English instruction. Using a qualitative approach with a participatory workshop model, the program included material presentations, group discussions, and lesson plan (RPP/ATP/Modul Ajar) simulations. Data were collected through observations, participant interviews, and documentation of workshop products. The findings show that the workshop significantly enhanced teachers’ competence in designing flexible and adaptive curriculum components aligned with the Merdeka Belajar framework. Participants demonstrated increased enthusiasm for implementing student-centered learning, character development, and communicative skill enhancement in English classes. Overall, the program contributes to supporting a more relevant, responsive, and student-centered education system in Maospati District.